Risk factors for developing a cutaneous injection-related infection among injection drug users: a cohort study - Tyndall Mark W; Zhang Ruth; Wood Evan; Lloyd-Smith Elisa; Montaner Julio SG; Kerr Thomas (BMC Public Health, 2008)
Abstract Background Cutaneous injection-related infections (CIRI), such as abscesses and cellulitis, are common and preventable among injection drug users (IDU). However, risk factors for CIRI have not been well described in the literature. We sought to characterize the risk factors for current CIRI among individuals who use North America's first supervised injection facility (SIF). Methods A longitudinal analysis of factors associated with developing a CIRI among participants enrolled in the Scientific Evaluation of Supervised Injecting (SEOSI) cohort between January 1, 2004 and December 31, 2005 was conducted using generalized linear mixed-effects modelling. Results In total, 1065 participants were eligible for this study. The proportion of participants with a CIRI remained under 10% during the study period. In a multivariate generalized linear mixed-effects model, female sex (Adjusted Odds Ratio (AOR) = 1.68 [95% Confidence Interval (CI): 1.16–2.43]), unstable housing (AOR = 1.49 [95% CI: 1.10–2.03]), borrowing a used syringe (AOR = 1.60 [95% CI: 1.03–2.48]), requiring help injecting (AOR = 1.42 [95% CI: 1.03–1.94]), and injecting cocaine daily (AOR = 1.41 [95% CI: 1.02–1.95]) were associated with an increased risk of having a CIRI. Conclusion CIRI were common among a subset of IDU in this study, including females, those injecting cocaine daily, living in unstable housing, requiring help injecting or borrowing syringes. In order to reduce the burden of morbidity associated with CIRI, targeted interventions that address a range of factors, including social and environmental conditions, are needed.